(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The reforms initiated by the President of the Republic of Uzbekistan Shavkat Mirziyoyev show the gratitude of our compatriots. Regardless of the field, new reforms are being introduced in every field today. This can be seen in political processes, science, agriculture, people’s life and youth life. The most gratifying situation for us is that our President Shavkat Mirziyoyev delivered a speech in Uzbek on September 20, 2023 at the next 78th session of the United Nations in New York, USA. This also gave us pride and honor. Today, about 50 million people worldwide speak the Uzbek language. Our beautiful and attractive Uzbek language is being studied with great enthusiasm in many countries.